Peningkatan Hasil Belajar IPS melalui Penerapan Model Pembelajaran Student Teams Achievement Divisions (STAD) pada Siswa Kelas IX di SMP Negeri 2 Keruak Masa Covid 19 Semester Ganjil Tahun Pelajaran 2021/2022 - Sapriadi, Sapriadi; Suryahayati, Suryahayati; Patimatuzzaharo, Patimatuzzaharo; Sopiatun, Sopiatun (TSAQOFAH, 2021)
Classroom Action Research aims to determine the improvement of social studies learning outcomes through the application of the Student Teams Achievement Divisions (STAD) Learning Model for Class IX students at SMP Negeri 2 Keruak during the Covid 19 Odd Semester for the 2021/2022 Academic Year. The procedure applied in each cycle includes the stages, namely (a) Action Planning, (b) Action Implementation (c) Observation and Evaluation (d) Reflection. In this study, there were 16 students who were divided into 4 groups. The research method used is a descriptive method in the form of direct observation research. Data collection techniques used are observations and documents with data collection tools, observation sheets and student test answers. In this classroom action research, it was carried out in 2 cycles, from the results of the actions taken it was proven to be able to improve student learning outcomes by achieving the specified classical completeness of 85%. Classical completeness 69% obtained in the first cycle, can be increased in the second cycle to 88%. In terms of student activity, there was also an increase, namely in the first cycle, the moderately active category increased to an active category. The results of this action research indicate that the application of the "Student Teams Achievement and Divisions" Learning Model can improve student learning outcomes in social studies lessons with completeness reaching 88%.